The impact of AMniotic FluId on the development and microBIal colonization of the prEterm intestinal tract (AMFIBIE): study protocol for a multicenter prospective cohort study - de Kroon, Rimke R.; van Weelden, Sofie; Monen, Loes; Bakker, Petra; Pajkrt, Eva; Struys, Eduard A.; Budding, Andries E.; de Meij, Tim; Niemarkt, Hendrik J.; van Weissenbruch, Mirjam M. (Frontiers in Pediatrics, 2026)
IntroductionPrematurity is associated with intestinal immaturity and gut microbiota alterations, both of which are linked to necrotizing enterocolitis (NEC) and sepsis. An important yet understudied contributor in the development of the gastrointestinal (GI) tract is amniotic fluid (AF). The aim of this study is to assess the composition of AF collected during extremely preterm birth. Secondary objectives are to identify AF profiles of pregnancies complicated with chorioamnionitis and/or fetal growth restriction, assess key AF components across gestation, correlate AF profiles with neonatal outcomes (e.g., NEC and sepsis), and explore associations with neonatal gut microbiota.Methods and analysisIn this multicenter prospective cohort study, AF (∼5 mL) will be collected from obstetric patients delivering their infants extremely preterm [gestational age (GA) 24 + 0/7–27 + 6/7 weeks, n = 125]. AF can be collected safely and non-invasively during vaginal delivery or cesarean section. AF samples will also be collected from a reference group (GA <23 + 6/7 and 28 + 0/7–40 + 6/7 weeks, n = 150). Characterization of AF will include microbial and metabolic profiling. By advancing our understanding of the role of AF in the GI development and neonatal disease, this study may contribute to the early identification of infants at risk to develop NEC and/or sepsis. Ultimately these findings may facilitate early targeted microbiota-based interventions to prevent disease progression and improve outcomes. While the current study provides clinical opportunities, several methodological challenges inherent to collecting AF at birth must be acknowledged, including variability in sampling method, maternal blood interference, and the risk of microbial contamination.Ethics and disseminationsEthical approval was received by the METC of the Máxima Medical Center in Veldhoven, the Netherlands (W24.042). The study was registered in a public clinical trial registry (NCT07152106). Study findings will be disseminated through peer-reviewed journal articles as well as national and international conference presentations.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT07152106, identifier NCT07152106.